Highly Sensitive Flexible Pressure Sensors Enabled by Mixing of Silicone Elastomer With Ionic Liquid-Grafted Silicone Oil - Kang, Zhaoqing; Nie, Yi; Yu, Liyun; Zhang, Suojiang; Skov, Anne Ladegaard (Frontiers in Robotics and AI, 2021)
Developing highly sensitive flexible pressure sensors has become crucially urgent due to the increased societal demand for wearable electronic devices capable of monitoring various human motions. The sensitivity of such sensors has been shown to be significantly enhanced by increasing the relative dielectric permittivity of the dielectric layers used in device construction via compositing with immiscible ionic conductors. Unfortunately, however, the elastomers employed for this purpose possess inhomogeneous morphologies, and thus suffer from poor long-term durability and unstable electrical response. In this study, we developed a novel, flexible, and highly sensitive pressure sensor using an elastomeric dielectric layer with particularly high permittivity and homogeneity due to the addition of synthesized ionic liquid-grafted silicone oil (denoted LMS-EIL). LMS-EIL possesses both a very high relative dielectric permittivity (9.6×105 at 0.1 Hz) and excellent compatibility with silicone elastomers due to the covalently connected structure of conductive ionic liquid (IL) and chloropropyl silicone oil. A silicone elastomer with a relative permittivity of 22 at 0.1 Hz, Young’s modulus of 0.78 MPa, and excellent homogeneity was prepared by incorporating 10 phr (parts per hundreds rubber) of LMS-EIL into an elastomer matrix. The sensitivity of the pressure sensor produced using this optimized silicone elastomer was 0.51 kPa-1, which is100 times higher than that of the pristine elastomer. In addition, a high durability illustrated by 100 loading–unloading cycles and a rapid response and recovery time of approximately 60 ms were achieved. The excellent performance of this novel pressure sensor suggests significant potential for use in human interfaces, soft robotics, and electronic skin applications.